Identification of digital innovation service performance indicators influencing UAE judicial system - Kudus, Norliah; Eidha Alkatheeri, Hamad Awadh Salem (RIS scientific Academy, 2024)
Objective: The global economic crisis has had a profound impact on youth unemployment, affecting young job seekers both directly and indirectly. As a result, they are confronted with limited job opportunities, which, in turn, elevates the risk of long-term unemployment. Furthermore, this crisis has created significant barriers to achieving financial independence through secure, stable employment. Therefore, this paper aims to examine the underlying causative factor of youth unemployment that have been exacerbated by the global economic crisis.